Pengaruh Suasana Toko dan Mutu Layanan terhadap Tingkat Kepuasan Pelanggan di Qahwa Coffee Shop & Entertain - Gey Des Four Munte; Khafi Puddin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of store atmosphere and service quality on customer satisfaction at Qahwa Coffee Shop & Entertain. The phenomenon of increasing competition in the coffee shop business requires managers to pay attention to the shop atmosphere and the quality of service provided in order to be able to create a positive experience for customers. The research method used was quantitative by distributing questionnaires to a number of respondents who are customers of Qahwa Coffee Shop & Entertain. The data analysis technique was carried out using multiple linear regression to determine the simultaneous and partial effects of independent variables on customer satisfaction. The results of the study indicate that store atmosphere and service quality have a positive and significant effect on customer satisfaction, both partially and simultaneously. This finding indicates that the better the shop atmosphere and service provided, the higher the level of customer satisfaction. This study is expected to be a consideration for the management of Qahwa Coffee Shop & Entertain in designing strategies to improve service quality and create a comfortable atmosphere that can strengthen customer loyalty.